Cognitive Discourse Analysis of Metaphor in Dhain’s 2020 Drama “Flower and Knife” - Abbood, Ansam Ghazi; Jamel, Heevi Khaled; Gargary, Khalid Ilias Basheer (Universitas Nusantara PGRI Kediri, 2024)
This paper presents a critical analysis of “FLOWER AND KNIFE” by Ahmed Yasir Dhain. It was written in 2020. The play represents two couple of notions “love and hate” “flower and knife